2020
DOI: 10.1155/2020/7194342
|View full text |Cite
|
Sign up to set email alerts
|

Video-Based Detection Infrastructure Enhancement for Automated Ship Recognition and Behavior Analysis

Abstract: Video-based detection infrastructure is crucial for promoting connected and autonomous shipping (CAS) development, which provides critical on-site traffic data for maritime participants. Ship behavior analysis, one of the fundamental tasks for fulfilling smart video-based detection infrastructure, has become an active topic in the CAS community. Previous studies focused on ship behavior analysis by exploring spatial-temporal information from automatic identification system (AIS) data, and less attention was pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 30 publications
0
79
0
Order By: Relevance
“…Weng et al used the association rules to determine crucial maritime accident contributory factors and mutual coupled effects on the ship detention incident [11]. Similar studies can be found in [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 90%
“…Weng et al used the association rules to determine crucial maritime accident contributory factors and mutual coupled effects on the ship detention incident [11]. Similar studies can be found in [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 90%
“…Note that we can obtain the friction coefficient value with two different working logics, which are empirical-like methods and the nonlinear relevant models. Previous studies suggested that solutions obtained by empirical relevant models may not be very robust, which may further degrade traffic modeling accuracy [28][29][30][31][32]. It is noted that the relationship between the friction coefficient and the typical traffic relevant factors (i.e., road conditions, tire structural parameters, and vehicle speed) is a type of nonlinear function.…”
Section: Calculation Of Road Surface Adhesion Coefficientmentioning
confidence: 99%
“…During braking, the deceleration of vehicle changes with time, as shown in Figure 2 [1,30]. Phase I is the reaction phase before performing, and Phase II is the coordination phase between the brake pedal and the vehicle.…”
Section: Analysis Of Vehicle Braking Processmentioning
confidence: 99%
“…Note that AIS is a type of self-reporting system originally designed for preventing potential accident, which is a mandatory facility for cargo ships (i.e., ship with gross tonnage larger than 300) [4][5][6][7][8]. Moreover, fishing boats with length longer than 15 m are required to install AIS equipment in the European Union Member States [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%